(untitled) (Research, Society and Development, 2021)
This study aims at presenting memes as a teaching technique and the students’ perspectives on the use of memes in education. Two groups of 35 and 31 students, ranged from 18 to 33 years old, enrolled in the entomology classes in a public university in Ecuador, participated in this project. The didactic sequence was put into practice from November 2020 to March 2021, and it was based on Marcuschi (2008). Students were asked to create a meme related to each unit of the course. To collect the data, one online questionnaire was used to get to know the participants’ perspectives at the end of the semester. The results showed that the participants saw the use of memes as an untraditional type of class with positive outcomes. Also, they saw memes as a fun tool for educational purposes. So, we consider memes an essential and powerful tool for education because they permit interactivity among students, raise curiosity, foster motivation, nurture critical thinking, and help students remember the previously learned content. Considering the positive outcome of this research, we believe this study is addressed for professors of higher education in the area of Entomology who seek new methodologies to be used in class.